2019
DOI: 10.1016/j.geoforum.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Production of scale in regional hydropolitics: An analysis of La Plata River Basin and the Guarani Aquifer System in South America

Abstract: This article analyses the production of scale in the La Plata River Basin and Guarani Aquifer System within regional hydropolitics in South America. We argue that different political and ecological scales acquire prominence according to the national political goals at stake, reproducing multi-scalar politics within and beyond South America. To support this argument, this article presents a literature review on the concept of scale in geography that explores the production of, and interaction among scales. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 33 publications
0
25
0
2
Order By: Relevance
“…The temporal scale is equally critical in nexus planning as it is essential in scenario planning (an important component of nexus planning) and for interpreting future climatic and environmental changes, resource availability or population projections at different time intervals [64]. Each spatial scale has its own dynamics, particularly when it comes to data availability [65].…”
Section: Way Forwardmentioning
confidence: 99%
“…The temporal scale is equally critical in nexus planning as it is essential in scenario planning (an important component of nexus planning) and for interpreting future climatic and environmental changes, resource availability or population projections at different time intervals [64]. Each spatial scale has its own dynamics, particularly when it comes to data availability [65].…”
Section: Way Forwardmentioning
confidence: 99%
“…The problem of overexploitation of groundwater resources is widespread in the Haihe River Basin, and the popularization rate of agricultural water-saving projects is relatively low in some areas. Groundwater resources are often over-exploited for agricultural uses in the Haihe River Basin, as well as in other basins around the world, from the Middle East to South America [35][36][37][38]. Research has shown how management of transboundary groundwater resources is more likely to happen at the local level rather than at the national or transboundary level, as users have a direct interest in preserving quantity and quality of its water [39,40].…”
Section: Arol Model Of Groundwater Exploitation Rate and Effective Irmentioning
confidence: 99%
“…Analysis [196] Water The mechanisms that were introduced by the political perspective focus on overcoming the constraints that are imposed by the political environment on transboundary water interactions in order to enable facilitating transboundary water conflict resolution. As Figure 10 shows, they do not address the technical or the economic process that are needed to resolve transboundary water conflicts.…”
Section: Explanationmentioning
confidence: 99%